The Influence Of Gender Diversity On Audit Opinions In The Consumer Goods Industry On The IDX - Nababan, Nindy Arine; Sari, Warsani Purnama (Economics, Business and Management Science Journal, 2026)
This research aims to analyze the impact of gender diversity on audit opinions in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) during the period from 2020 to 2023. Gender diversity in this study is proxied by the presence of women on the board of commissioners and the board of directors. This study uses a quantitative approach with a causal associative method. Samples were determined using purposive sampling techniques from 31 companies over a period of 4 years with a total of 124 observation data. The data were analyzed using binary logistic regression. The results of the study indicate that, partially, the presence of a Women’s board of commissioners does not have an effect and a Women’s board of directors has a positive and significant effect on audit opinions, while simultaneously, the presence of the board of commissioners and board of directors has a positive and significant impact on audit opinions.